2019
DOI: 10.1016/j.jadohealth.2019.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Only Yes Means Yes: Sexual Coercion in Rural Adolescent Relationships

Abstract: Sexual Coercion Among Rural Adolescents 2 Implications and ContributionConsent is essential to healthy adolescent relationships, but sexual consent and coercion are under-studied in rural youth. In our study, youth from a rural high school commonly experienced sexual coercion, and female and male students identified different modifiable risk and protective factors.Sexual Coercion Among Rural Adolescents 3 ABSTRACT Purpose: Sexual consent is important to healthy relationships; however sexual coercion is common.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 8 publications
0
20
0
Order By: Relevance
“…The study also showed a signi cant association between earlier onset of sexual relations among young females and greater risk of sexual coercion. This is supported by the reports from studies conducted elsewhere, explaining for being earlier age is vulnerable to unwanted sexual intercourse and young female who initiated sex at very young ages may also have experienced some sort of pressure either physical or verbal to have sex against their will [4,6,22,28].…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…The study also showed a signi cant association between earlier onset of sexual relations among young females and greater risk of sexual coercion. This is supported by the reports from studies conducted elsewhere, explaining for being earlier age is vulnerable to unwanted sexual intercourse and young female who initiated sex at very young ages may also have experienced some sort of pressure either physical or verbal to have sex against their will [4,6,22,28].…”
Section: Discussionmentioning
confidence: 56%
“…Sexual coercion is the act of being physically, psychologically, nancially or otherwise forced or tricked into engaging in sexual activity [1,2]. Most commonly the victims of sexual coercion are women and children [3,4]. These includes acts of being worn down by someone who repeatedly asks for sex being lied to or being promised things that weren't true to trick you into having sex; having someone threaten to end a relationship or spread rumors about you if you don't have sex with them; and having an authority gure, like a boss, property manager use their in uence or authority to pressure young female into having sex [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this space, the role of psychology intervenes, the willingness to interpret, understand what the other person wants to tell and pretends to communicate, even without saying a word. Thus, the complexity of defining consent is not so much its definition, but its applicability (Katz et al, 2019). While there is a quiet widespread agreement on the way consent is defined, the debate is driven to know exactly what consent does involve and the context surrounding it (Muehlenhard et al, 2016).…”
Section: Consent From Speech Acts To Communicative Actsmentioning
confidence: 99%
“…Duress and coercion also exist in relationships between teenagers. In a study conducted by Katz et al (2019), 422 students between the ages of 15 and 16 were surveyedwith just one question: "Did someone with whom you are dating or with whom you dated, force you to do sexual things that you did not want to do?" The results showed that approximately 22% of women and 8% of men reported having experienced sexual coercion at least once in their life.…”
Section: Introductionmentioning
confidence: 99%